DEVELOPMENT OF REAL TIME POLYMERASE CHAIN REACTION FOR DETECTION OF Salmonella typhimurium AND Salmonella enteritidis IN FISH - Tuti Hartati Siregar; Jennifer Elliman; Leigh Owens (Squalen, Buletin Pascapanen dan Bioteknologi Kelautan dan Perikanan, 2012)
Previously designed endpoint PCR has been adapted for use with real time PCR to detect the presence of Salmonella typhimurium and Salmonella enteritidis  in fish. Optimization of a standard curve in the presence of herring sperm DNA as background matrix indicated that the real time PCR highly efficient with the Pearson coefficient of determination (R2) value = 0.99937 and slope (M) value = -3.44. An enrichment method (overnight culture) significantly increased (p0.05) the sensitivity of real time PCR. Comparison of real time PCR and the conventional isolation method based on biochemical tests has been conducted. In terms of their sensitivity, real time PCR and the conventional methods are not significantly different in the level of confidence 95%. Both real time PCR with enrichment method and conventional biochemical method can detect the presence of Salmonella spp. in spiked sample. However the direct extraction method was only detecting the presence of Salmonella in higher concentration. While the sensitivity both conventional and real time PCR are similar, the real time PCR has an advantage to detect the pathogen qualitatively and quantitatively depending on processing method.